Comic Media on Arabic Language Learning Speaking Skills: The Analysis of Students’ Creative Thinking - Saniyyah, Azzah; Fatim, Al Lastu Nurul; Musdalifah, Musdalifah; Hamid, M. Abdul (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2024)
Abstract. The active involvement of students when learning Arabic language speaking skills using comic media has implicitly raised and produced the process of creative thinking ability. The creative thinking ability produced by students during the learning process can be reviewed in more detail based on its aspects. According to Guilford, this study aims to reveal the utilization of comic media for Arabic speaking skills to improve creative thinking. This study includes qualitative research using a case study design with a type of single case instrument that produces descriptive data. The descriptive data was collected by 1) observation of the learning process, 2) distribution of observation results and their classification on Guilford's creative thinking ability, and 3) data disclosure and reporting. The selection of participants used a purposive sampling technique on 32 ninth-grade students.  Using the interactive model for analysis technique by identifying comic media developed and implemented to describe and classify all learning activities from speaking skills to creative thinking ability based on Guilford's theory. The study's findings show that four different comic activities, all of which improve students' ability for creative thought when learning to speak Arabic, namely: a) dialog, including associational fluency, expressional fluency, and originality; b) survey, including associational fluency, ideational fluency, and spontaneous flexibility; c) development of description, featuring associational fluency, ideational fluency, and spontaneous flexibility; d) storytelling, including ideational fluency, expressional fluency, and originality. Using students' imaginations and experiences employing comics as a teaching tool for speaking skills can enhance and promote creative thinking.  This creative thinking during Arabic language learning has created active student engagement to communicate actively and confidently, driving the improvisation of speaking skills.Keywords: Arabic Speaking Skills, Comic Media, Creative Thinking